STRATEGI INDONESIA MEMANFAATKAN PELUANG EKSPOR KE PASAR AFRIKA SELATAN (2010-2014) - Artika Ayu Wulaningrum (HI 15 UMY 398, 2015)
*398 This research focuses in the Indonesian strategies utilizing export opportunities to the South African Market. The International trade has provided many impacts in Indonesia, such as economy, social and politic. Indonesia’s policy has decided that the government system, Democracy, brought the nation to the international level where free trade area has established as international market. As one of the nations who ratified the treaty in World Trade Organization, Indonesia’s government looking forward to increased economic standard and stabilized politic with increasing international trade, especially export and import in South Africa. The result of the economic percentage based on government statistics, Indonesia leads above world’s result. In order to keep the stability, government made the economic agreements based on reciprocity as the strategy of Indonesian domestic politics